Heen Binkohoba , Andrographis paniculata (Burm. f.) Wall. ex Nees - Weerakoon, W.A.S.S.; Perera, P.K. (Sri Lanka Journal of Indigenous Medicine (SLJIM), University of Colombo, 2020)
The plant, Andrographis paniculata (Burm.f) Nees, grows as an erect herb to a height of 30-110 cm (12-43 in) in moist ...